Philippe Guimiot art gallery : 1984. - Philippe Guimiot Art Gallery, Brussel (Bruxelles : Philippe Guimiot art gallery, 1984)
Armodio ; Koenraad ; Carron ; Arisman, Marshall ; Olsson, Johannes ; Améal ; Foppiani, Gustavo ; Coenen, Jean ; Arboleda, Alberto ; Guarienti, Carlo ; Madlener, Jörg
boek